Policy Analysis, Implementation and Future Prospects of JFM in India - Bahuguna, V. K.; , Hilaluddin (Indian Forester, 2011)
This article reviews policy and institutional framework set up for implementation of Joint Forest Management Programme in India. Initially, the growth of JFM was tardy and slow during first initial decade due to lack of proper institutional arrangements. The MoEF revised JFM guidelines in 2000 and 2002 and circulated these guidelines among all States and Union Territories with sharpen focus on extending JFM programme to good forests with very well defined institutional and legal framework. Consequently, JFM movement in the country progressed both quantitatively as well as qualitatively. As of 2007, more than one lakh JFMCs had been managing around 22 million ha of forestland. Out of 1.6 million reported forest fringe villages in the country, roughly 62% forest fringe villages have been covered under JFM stream with involvement of around 8.3 million families and 62 million people.